Filamin B extensively regulates transcription and alternative splicing, and is associated with apoptosis in HeLa cells - Ma, Hai-Rong (Oncol Rep, 2020)
Post-transcriptional mechanisms are an important approach in the treatment of cancer, and may also be hijacked by tumor cells to help adapt to the local microenvironment. Filamin B (FLNB), an actin-binding protein that provides crucial scaffolds for cell motility and signaling, has also been identified as an RNA-binding protein. Recent studies demonstrated that FLNB might play an important role, not only in skeletal development, but also in regulating tumorigenesis; however, the effects of dysregulated expression of FLNB at the molecular level are not clear. In the present study, RNA-sequencing was performed to analyze changes in overall transcriptional and alternative splicing between the knocked-down FLNB and the control in HeLa cells. Decreased FLNB levels resulted in significantly lower apoptosis compared with control cells. FLNB knockdown extensively regulated the expression of genes in cell apoptosis, tumorigenesis, metastases, transmembrane transport and cartilage development. Moreover, FLNB regulated alternative splicing of a large number of genes involved in ‘cell death’ and the ‘apoptotic process’. Some genes and alternative splicing related to skeletal development were enriched and regulated by FLNB. Reverse transcription-quantitative-PCR identified FLNB-regulated transcription and alternative splicing of genes, such as NLR family apoptosis inhibitory protein, interleukin 23 subunit α, metastasis associated lung adenocarcinoma transcript 1, phosphofurin acidic cluster sorting protein 2, bone morphogenetic protein 7, matrix metallopeptidase 13, collagen type II α 1 chain, fibroblast growth factor receptor 2 and vitamin D receptor. The present study is the first study, to the best of the authors’ knowledge, to provide transcriptome-wide analysis of differential gene expression and alternative splicing upon FLNB silencing. The present results suggested that FLNB may play an important regulatory role in cervical cancer cell apoptosis via regulation of transcription and alternative splicing, which provide insight for the current understanding of the mechanisms of FLNB-mediated gene regulation.